Steel binder cermets processed by combination of colloidal processing and powder metallurgy. (August 2018) - Alvaredo, P.; Escribano, J.; Ferrari, B.; Sánchez-Herencia, A.J.; Gordo, E.
Abstract: Cermets constituted by a high-speed steel matrix reinforced with 50 vol% Ti(C, N) present a great potential due to its combination of properties, such as high wear and oxidation resistance, together with high values of hardness and toughness. However, the consolidation of these materials by conventional powder metallurgy processing presents two main problems: The agglomeration of Ti(C, N) particles, leading to non-homogeneous microstructures, and the low compressibility of the blends due to the small size and morphology of the starting powders. In this work, colloidal techniques are proposed to overcome these issues. Aqueous suspensions of steel powders and Ti(C, N) particles are prepared followed by spray-dry to obtain spherical granules able to be processed by pressing and sintering, avoiding oxidation of powders. The agglomerates present higher compressibility than blends, and sintered materials show higher density and hardness. Highlights: Colloidal processing of a metal ceramic compound material to produce granules from aqueous suspensions. Improvement of compressibility of the powders. More homogeneous microstructures with higher hardness.